2011
DOI: 10.2754/avb201180010029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibacterial effect of seven 1-monoglycerides on food-borne pathogens or spoilage bacteria

Abstract: The aim of this study was to compare under the same conditions in vitro the inhibitory effects of seven 1-monoglycerides (MAG) containing fatty acids with a medium chain on ten strains of food-borne pathogens or spoilage gram-positive and gram-negative bacteria (Bacillus cereus, Bacillus subtilis, Enterococcus faecalis, Micrococcus luteus, Staphylococcus aureus, Citrobacter freundii, Escherichia coli, Proteus mirabilis, Salmonella enterica ser. Enteritidis and Pseudomonas aeruginosa) and on their growth indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
4
27
0
Order By: Relevance
“…1 and Fig. 2), indicating that these fatty acid esters did not inhibit spore germination. These results are consistent with previous reports (Buňková et al, 2011;Kuwana et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…1 and Fig. 2), indicating that these fatty acid esters did not inhibit spore germination. These results are consistent with previous reports (Buňková et al, 2011;Kuwana et al, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…These hydrophobic fatty acid esters that have high affinity for the lipid bilayer membranes of microorganisms are well incorporated by microorganisms, and show strong antibacterial effects (Buňková et al 2011). Fatty acid esters also may adsorb to the bacterial surface, where the esters induce damage and the leakage of intracellular substances (Kuwana et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Monoacylglycerols are normal part of the digestion of lipids and are widely used in the food industry as emulsifiers (Moonen & Bas 2004). Monoacylglycerols containing MCFAs have been shown to be efficient antimicrobial agents in cultures of food-borne pathogens, bacteria that are associated with spoilage, and fungi (Buňková et al 2011). Reports on the effects of capric acid, lauric acid, and monocaprin on Cronobacter, which is a Gram-negative bacterium and thus less susceptible to antimicrobials relative to Gram-positive bacteria, are absent from the current literature.…”
Section: Dbm 3157mentioning
confidence: 99%
“…There were lot published literatures to prove the inhibitory property of various MAGs against Grampositive bacteria (Kabara et al, 1972;Schlievert et al, 1992;Oh and Marshall, 1993;Branen and Davidson, 2004;Bunkova et al, 2011) and the resistant property to Gramnegative bacteria (Skrivanova et al, 2006;Kabara, 1978;Kabara, 1984). Based on detailed published studies of saturated fatty acids with chain lengths between 6 and 18 carbons, the lauric acid was found to possess more inhibitory activity against Gram-positive bacteria (Kabara et al, 1972) and MAG synthesized with caproic acid and caprylic acid in our study were found to show similar inhibitory effect.…”
Section: Anti-bacterial Effectmentioning
confidence: 98%